Análise da aquisição de bens de capital na UFSCar campus Sorocaba: a inserção de critérios ambientais nas requisições - Zagues, Fábio Fernandes (Universidade Federal de São Carlos, 2018)
Public entities use the legal means to acquire their durable goods, which are acquired through bids, regulated by Federal Law No. 8.666 / 1993. In order for these bids to reach a higher level of success, it is necessary that the requests have very well-defined Terms of Reference, providing all conditions for the acceptance of the desired good, including environmental criteria. In this way, the present work aims to identify if the requesters insert in the Terms of Reference the environmental criteria set forth in Federal Decree n.º 7.746/2012. As methodology was used the qualitative research, having as a bibliographical and documentary research procedure. We identified in the Terms of Reference how many requests have environmental criteria and in the Minutes of the trading sessions it was observed whether the bidders can meet these requests. After analyzing the data, it was possible to verify that, although there are many laws, they are generally not sufficiently disseminated among the servers, so that they are not fully implemented. Thus, the paper presents an improvement proposal consisting of a table containing all the environmental criteria available in the specific legislation to be used in the next requisitions. The results point to the need to invest in training the servers so that everyone knows the available environmental criteria and, finally, the search opens new avenues for new follow-ups in the future bidding processes, contributing to a better environmental management. within public bodies.
Analysis of the acquisition of capital goods in UFSCar campus Sorocaba: the insertion of environmental criteria in the requisitions.
Keywords: Compras públicas; Critérios ambientais; Termos de referências; Public procurement; Environmental criteria; Terms of reference; Licitação pública; Letting of contracts; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA TEORICA